Mechanistic aspects of preheating effects of precursors on characteristics of Cu2ZnSnS4 (CZTS) thin films and solar cells. (July 2019) - Long, Bo; Cheng, Shuying; Ye, Dapeng; Yue, Chuang; Liao, Jie
Graphical abstract: Highlights: The Cu2 ZnSnS4 (CZTS) films are prepared by sol-gel method following sulfurization. The defects at the interface of CZTS thin film and Mo foil make the electrical properties of solar cell worse. The Mo layer inserted between CZTS thin film and Mo foil has the effects on the properties of solar cell. The flexible CZTS TFSC with Mo layer inserted has a conversion efficiency of 1.58%. Abstract: CZTS thin films are fabricated using sol-gel method following sulfurization. The material properties of the CZTS films which are prepared under different preheating temperatures and times are systematically investigated. The TGA-DTA analysis shows that the sulfides begin to be oxidized and the CZTS nanoparticles would be formed when the preheating temperature is above 300 °C. Moreover, with increasing the preheating temperature and time, the crystallinity of the CZTS thin films becomes stronger firstly and then weaker. Morphological characterizations show that the CZTS thin films deliver the best crystallinity under the preheating temperature of 250 °C for 5 min. The Eg, resistivity, carrier concentration, and mobility of the CZTS thin films is 1.45 eV, 3.56 Ω·cm, 2.47 × 10 17  cm −3, 7.12 cm 2 ·V −1 ·s −1, respectively. The solar cells with the efficiency of 1.51% is successfully configured.